Conflict and Conflict Resolution in Ghana: The Case of the Dagbon Conflict - Carscious, A.E. (University of Ghana, 2013)
The African continent has witnessed a number of bloody conflicts since the end of the cold war leading to serious consequences including political, social, economic and humanitarian problems. Although Ghana enjoys considerable peace compared to Cote d’Ivoire, Liberia, Sierra Leone and others, it is venerable to intermittent communal violence as well as ethnic and chieftaincy conflicts. The Northern Region, in particular has witnessed protracted conflicts over chieftaincy such as the succession dispute between the Abudu and Andani Royal Families of the Dagbon Kingdom. Analysing data from both primary and secondary sources, the study found that although unemployment, particularly among the youth, has caused social upheavals, the conflict in Dagbon is directly linked to chieftaincy. The two Royal gates, Abudus and Andanis have failed to abide by the laid down framework on succession to the skin. These have evoked tension, mistrust and suspicion among the two families thereby slowing development programmes in the area. Given the dynamics of the conflict, only an independent body particularly, non-state actors such as Civil Society Organisations (CSOs) have the wherewithal to instigate a peaceful solution to the conflict.
Thesis (MPhil)-University of Ghana, 2013